AIRA Chatbot for Travel: Case Study of AirAsia. (April 2020) - Kasinathan, Vinothini; Wahab, Mohd Helmy Abd; Idrus, Syed Zulkarnain Syed; Mustapha, Aida; Yuen, Kho Zhi
Abstract: Tourism is one of the main economic contribution to many countries worldwide. This paper presents an Artificial Intelligence tool to help improve the performance, quality and credibility of customer service for AirAsia Berhad, a renowned local business in travel/airline industry in Malaysia. The tool, AIRA, is developed using C# in Verbot 5.0 and plays an important role as an information gatherer, gathers all the latest and correct information in order to provide the best service to customers. The evaluation has proved that AIRA provided a simple, easy to navigate GUI with high efficiency, hence a user-friendly system that requires little or no technical knowledge to operate. AIRA is hoped to improve the quality of customer service in AirAsia by giving an alternative to entertain travellers.